PENGGUNAAN MODEL NUMBERED HEADS TOGETHER (NHT) DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - HARTANTI, TITIN (KALAM CENDEKIA PGSD KEBUMEN, 2013)
Abstract: The use of Model Numbered Heads togather (NHT) in Mathematics Teaching in Elementary School. Mastery of the material on the subjects Mathematics students are very low, as evidenced by the low yield Teaching Mathematics. In order for the teachers to learn mathematics better using NHT models in learning Mathematics. The purpose of this study to describe the steps using NHT models in learning Mathematics in Primary Schools. This study used tektik classroom action research. The results showed that the use of NHT models can improve learning outcomes in primary school mathematics. Keywords:Teaching, NHT, Math. Abstrak: Penggunaan Model Numbered Heads Togather (NHT) dalam Pembelajaran Matematika di Sekolah Dasar. Penguasaan materi pada mata pelajaran Matematika siswa sangat rendah, terbukti dengan rendahnya hasil belajar Matematika. Agar hasil belajar Matematika lebih baik guru menggunakan model NHT dalam pembelajaran Matematika. Tujuan penelitian ini untuk mendeskripsikan langkah-langkah penggunaan model NHT dalam pembelajaran Matematika di Sekolah Dasar. Penelitian ini menggunakan tektik Penelitian Tindakan Kelas. Hasil penelitian menunjukkan bahwa penggunaan model NHT dapat meningkatkan hasil belajar Matematika di Sekolah Dasar. Kata Kunci: Pembelajaran, NHT, Matematika.